Cognitive development and children's perceptions of fruit and vegetables; a qualitative study - Kok Frans J; Koelen Maria A; Zeinstra Gertrude G; de Graaf Cees (BMC, 2007)
Abstract Background Most children do not meet the recommended guidelines for fruit and vegetable intake. Since preference is an important predictor of intake, more knowledge is needed about children's preferences and about how these preferences develop. As most research about preferences has ignored cognitive development, this study was designed to explore the relation between children's perceptions and preferences for fruit and vegetables and their cognitive development. Methods The study population consisted of eight 4-5-year-old children, eight 7-8-year-old children and twelve 11-12-year-old children, recruited via a primary school in Wageningen, The Netherlands. Qualitative in-depth information was obtained by duo-interviews and focus group discussions. A structured guide with questions and game tasks was applied to address different domains in a consistent way. Results The developmental progress at the abstraction level was seen in children's reasoning across all domains. Children's preferences expanded and increased in complexity as they moved to a higher age bracket. The most important determinants for liking and disliking shifted from appearance and texture attributes in 4-5-year-olds towards taste attributes in 11-12-year-olds. Children's knowledge of basic tastes increased. Their understanding of health improved as they grew older. The emergence of social norms and perspectives of others as the children grew older was also seen in relation to fruit and vegetables. Child-reported parental strategies to stimulate healthy eating appeared to vary with age in line with cognitive development. Conclusion Cognitive development is paralleled by changes in the importance given to the attributes that determine whether a child likes or dislikes fruits and vegetables; children's understanding of and reasoning about health; and parental use of strategies. These developmental differences should be incorporated in programs designed to increase long-term fruit and vegetable intake in children.